Weak Solution to a Parabolic Nonlinear System Arising in Biological Dynamic in the Soil - Côme Goudjo; Babacar Lèye; Mamadou Sy (International Journal of Differential Equations)
We study a nonlinear parabolic system governing the biological dynamic in the soil. We prove global existence (in time) and uniqueness of weak and positive solution for this reaction-diffusion semilinear system in a bounded domain, completed with homogeneous Neumann boundary conditions and positive initial conditions.